CSR Contextualization for Achieving the SDGs in Indonesia - I Kadek Agus Setiawan; Puji Ayu Larasati; Irwan Sugiarto (Journal of Judicial Review, 2021)
Companies in Indonesia carry out corporate social responsibility (CSR) on the basis of taking care of contractual obligations, in this case complying with regulations made by the central and local governments. Normatively, ideally without contractual obligations, the company should not care about profits, but also care about the welfare of the community and environmental sustainability. This research wants to examine and reveal the relationship between CSR in realizing Sustainable Development Goals (SDGs) in Indonesia. The research method used is the juridical-normative research method. Supporting this juridical-normative research using a statutory approach, a historical approach, and a conceptual approach. The data needed in this research is secondary data obtained by using library research techniques. This research shows that Indonesia is a country that requires parties to implement CSR through regulations. There is a close relationship between CSR and sustainable development because CSR puts forward 3 principles, namely economy, society, the environment which are then in accordance with the goals of sustainable development. CSR is a sustainable commitment by the business world that acts as action and contributes to the community's economy and environmental sustainability. Therefore, SDGs can be contextualized as a viewpoint for every company in its business activities through various CSR activities such as greening programs, providing clean water facilities, improving settlements, increasing welfare, improving the quality of education, and other things related to sustainable development.